2008
DOI: 10.1111/j.1365-3180.2008.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotation effects on Cyperus rotundus and C. esculentus population dynamics in southern California vegetable production

Abstract: Summary Control options for Cyperus rotundus and Cyperus esculentus (purple and yellow nutsedge) were evaluated within three cropping systems in the low desert of southern California: (1) standard vegetable crop rotation (weed‐free, uncontrolled nutsedge and cultivation) with spring cantaloupe (Cucumis melo) – summer fallow – winter broccoli (Brassica oleracea), (2) cover crop rotation (halosulfuron and smother crop) with spring wheat (Triticum aestivum)/corn (Zea mays) – summer sudangrass (Sorghum sudanense) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Its rapid spatial development and LCA expansion motivated modeling its spatial growth (Wang et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Its rapid spatial development and LCA expansion motivated modeling its spatial growth (Wang et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was also found that the CR plant density was higher in both cover plant species in the presence of opaque plastic sheet treatment as compared to that in the absence of the opaque plastic sheet. Although soils covered with the plastic sheet was observed to elevate the temperature in the air space (between the sheet and soil surface) and the upper soil [51], it was found that no negative effect on the tuber reproduction unless the upper soil temperature was elevated up to 45 • C and persisted for more than 7 h per day [52]. Moreover, studies indicated that phenolic compounds released from apple residues decreased with the elevating soil temperature [53].…”
Section: The Influence Of B Pilosa Var Radiata On the Reproduction mentioning
confidence: 99%
“…Although mechanical and physical methods (i.e. solarization) have been reported as effective control measures for other spring‐emerging perennial weeds (Wang et al. , 2008), S. halepense management is still largely based on herbicide application.…”
Section: Introductionmentioning
confidence: 99%